O projeto de atendimento ao desenvolvimento da aprendizagem ADA na Rede Municipal de Ensino de Uberlândia. O que sua história nos conta? - Lemes, Noemi Mendes Alves (2012)
This research aims to examine the process of organization and operation of Project ADA (Attendance to Learning Development), from 2007 to 2010 in Uberlandia\'s municipal education network. We had a mind to perceive the results and impacts of the quoted project in schools\' pedagogic projects. We relied on the qualitative approach, aiming the reaching of goals and the problematic. We utilized the documental analysis, the questionnaire; the semi structured interview and the focal group in two schools; one attending first to fifth grade students and the other attending first to ninth grade elementary students to collect data. For these analyses we organized thematic groups that pass by checking the relation between the proposed aims and the actions that ADA develops; the knowledge of Project ADA\'s headway and limits and the determining factors for its accomplishment in these schools. We verified that Project ADA was based on the psycho-pedagogic perspective that comprehends the appearing of the learning difficulty as part of a learning process. So, Project ADA\'s emerged as a repairing measure that has occurred from the injury caused by an excluding educational system, with ideological elements that, as a paradox, hamper the development of an education of good quality for all. The investigation showed traces that the start and development of this project brought a good difference in the attending process of students with learning difficulties. The actions made were in accord with the proposed aims and the results were helpful to the learning process of these attended students. We also confirmed that the implantation of Project ADA caused a positive impact in the schools and brought benefits for the teachers in their pedagogic practice. Nevertheless, some limiting factors became evident, which were superficially used by SME to end the project.